Issues on compensation for damage caused to patients in the provision of healthcare services - Mackevič, Laura; Mečanec, Dominykas (Vilnius University Open Series, 2024)
Health is one of the most important values of the individual and of society, which calls for a specific model of legal regulation and compensation that best serves the interests of the individual and society. In Lithuania, the new version of the PTŽSAĮ, which entered into force on 1 January 2020, introduced a no-fault model of compensation (administrative model). Analysing the relationship between the newly entered into force model of no-fault compensation (administrative model) and the previously existing model of judicial action, it would be incorrect to state that only the model of no-fault compensation (administrative model) is currently in operation in Lithuania, given the exhaustive list of the persons entitled to apply for non-pecuniary damages, which has been established by the current wording of the PTŽSAĮ, however, according to the authors of the article, by abolishing the exhaustive list of persons entitled to claim compensation for non-pecuniary damages and allowing all persons who have suffered damages as a result of inadequate provision of healthcare to a patient to claim compensation on the basis of the model of no-fault compensation (the administrative model), it would be reasonable to say that the model of no-fault compensation (administrative model), which has been put into force, has indeed changed (is in a position to change) the model of judicial action. Having established that there is reason to believe that the model of no-fault compensation (administrative model) will completely replace the model of judicial action in the future, the authors of the article draw attention to the existence of legal issues related to the implementation of the principle of full compensation in the event of the death of a foetus. Having established that a foetus has a limited right to health and life from the 12th week of pregnancy and a full right to life from the 22nd week of pregnancy, but there is currently no legislation in Lithuania to protect the health of the foetus, it can be concluded such situation raises the problem of the implementation of the principle of full compensation for damages. One potential solution to the problem could be the application of a legal fiction in relation to the foetus in the context of the PTŽSAĮ, as this would ensure the foetus’ right to life and health and justice.